Decision-Making Processes Used by Malaysian Managers of Small and Medium-Sized Enterprises When Deciding Their Participation in Government Sponsored Training Programs - Hana, Binti Hamidi (Universal Publishers, 2021)
This study identified the decision processes used by managers from small and medium-sized enterprises (SMEs) to participate in training programs funded by governments in Malaysia. Evidence has found that small and medium-sized businesses are vital to the economic growth of a country, and government-provided training programs may help foster organizational efficiency. Research has, however, revealed that SME participation is relatively low. Until now, there has been little research about how SME managers make decisions about how to send their workers to government-sponsored training programs, which could theoretically benefit the company. The study used the methods outlined by Willig (2013) for interpretative phenomenological analysis. Eight participants contributed to the study. Data collection was carried out in two stages. The first phase involved an in-depth, semi-structured interview of individuals. Phase two involved a group discussion. The group session included four SME executives. Added to the data were field notes from the author and reflective journal. Data were analyzed using the guidelines outlined in the IPA method adopted by Willig (2013). The findings revealed two major categories of the decision-making processes made by SME managers with two subcategories each. The first category is procedural strategies. The subcategories are collecting of information and processing of information. The second category is emotion orientation of SME managers when making decisions. The first subcategory is protecting the family business. The second subcategory is the use of gut feelings. Based on these findings, the study has addressed policy consequences, recommendations and limitations.